Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jcp.27755
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of pancreatic β‐cell dysfunction: Oxidative stress, microRNA, and long noncoding RNA

Abstract: Metabolic syndrome is known as a frequent precursor of type 2 diabetes mellitus (T2D). This disease could affect 8% of the people worldwide. Given that pancreatic β‐cell dysfunction and loss have central roles in the initiation and progression of the disease, the understanding of cellular and molecular pathways associated with pancreatic β‐cell dysfunction can provide more information about the underlying pathways involved in T2D. Multiple lines evidence indicated that oxidative stress, microRNA, and long nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 183 publications
(308 reference statements)
0
39
0
Order By: Relevance
“…9,10 Increasing reports indicate that lncRNA regulates the development and progression of human cancers. [11][12][13] LncRNAs may regulate proliferation, invasiveness and differentiation of tumor cells. 14 For example, HOXC-AS2 promotes metastasis of glioma cells by promoting ZEB1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Increasing reports indicate that lncRNA regulates the development and progression of human cancers. [11][12][13] LncRNAs may regulate proliferation, invasiveness and differentiation of tumor cells. 14 For example, HOXC-AS2 promotes metastasis of glioma cells by promoting ZEB1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, studies have demonstrated that several miRNAs regulate the expression and function of genes involved in pathways leading to oxidative stress in β cells and in tissues involved in diabetic chronic complications [8,9]. Therefore, it could be important to develop therapeutic strategies based on the modulation of the expression of these miRNAs, in order to inhibit or stimulate their activity and to partially relieve cellular dysfunctions caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs, 18–25 nucleotides in length, are noncoding RNAs that are able to target mRNAs and regulate their expression . In terms of functionality, miRNAs are important agents for gene silencing and post‐transcriptional regulation of proteins.…”
Section: Mirnas As Diagnostic and Prognostic Biomarkers In Hiv Infectionmentioning
confidence: 99%